Anomalous cerebral morphology of pregnant women with cleft fetuses - Li, Zhen; Li, Chunlin; Liang, Yuting; Wang, Keyang; Wang, Li; Zhang, Xu; Wu, Qingqing (Frontiers in Human Neuroscience, 2022)
Objective Pregnancy leads to long-lasting changes in brain structure for healthy women; however, little is known regarding alterations in the cortical features of pregnant women with malformed fetuses. Isolated clefts of the lip and/or palate (ICL/P) are the most common congenital anomaly in the craniofacial region, which is highly gene-associated. We speculated that pregnant women carrying fetuses with ICL/P may have associated risk genes and specific brain changes during pregnancy. Methods In this study, we investigated T1-weighted brain magnetic resonance imaging data from 48 pregnant women: 24 women carrying fetuses with ICL/P (ICL/P group) and 24 women carrying normal fetuses (normal controls), then explored intergroup differences in gray matter volume (GMV), cortical thickness (CT) and cortical complexity (gyrification). Results Compared with controls, the ICL/P group had decreased total intracranial volume (TIV) than normal controls; besides, they exhibited increased GMV in the left cuneus, decreased GMV in the right superior temporal gyrus; increased CT in the left precuneus and left superior parietal gyrus, decreased CT involving parsopercularis, fusiform, middle temporal in the left hemisphere and supramarginal, precentral gyrus (PreCG) in the right hemisphere; increased gyrification in the left insula and PreCG, the left middle temporal, and the right supratemporal gyrus. Conclusion Pregnant women with ICL/P fetuses had brain morphology changes involving language, auditory, vision, and sensory cortex, which may be their special brain changes compared to normal pregnant women. This study may provide clues for the early detection of fetuses with ICL/P, and be vital for preconception and prenatal counseling with non-invasive methods.